Prevenção às violações de direitos humanos no âmbito corporativo : perspectivas do criminal compliance e da responsabilidade penal da pessoa jurídica - Papa, Louise de Barros Ibarra (2022)
The dissertation seeks to examine, under a predominantly theoretical-legal focus of monographic and literature research, the umbilical relationship between human rights and corporations, taking into account that, in the scenario of globalization, large companies have emerged as a new influential agent in the international reality, raising concerns about the damage caused by its activities and the absence of a regulatory framework to promote the prevention of potential human rights violations. The perspectives brought by the criminal sciences are present as a spectrum of analysis, notably in the areas intended to investigate corporate crime as possible sources of conjugation of efforts in the promotion of human rights in corporations. The research hypotheses bring criminal compliance and criminal liability of the legal entity as possible mechanisms to stimulate the search for the effective prevention of corporate crime, as well as corporate violations of human rights. In the first section, the work analyzes the international protection of human rights and the new ways to promote them in face of socially harmful corporate activity; then, it points to the understanding of corporate illegality and inflows from the international anti-corruption law (a broad concept, which encompasses corporate crimes) permeating the theme from incursions of criminal policy, economical criminology and corporate victimology; finally, it approaches the theoretical contributions of the implementation of compliance programs and the adoption of autonomous criminal liability of the legal entity, using the ideas from the previous sections as guidelines to reflect about the necessary corporate prevention of human rights violations.